2008
DOI: 10.1111/j.1755-6686.2008.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cognitive Impairment in Patients Attending Pre‐dialysis Clinic

Abstract: Approximately 20-30% of patients on renal replacement therapy (RRT) have cognitive impairment. Less is known about the prevalence of cognitive impairment in patients with advanced kidney disease awaiting the initiation of dialysis. Routine cognitive assessment was implemented in the pre-dialysis clinic, which enabled the Nephrologist and Pre-dialysis Nurse to identify those patients with impaired cognitive function and utilise this information to assess the suitability for self-care treatments, such as periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
1
15
2
Order By: Relevance
“…However, a recent study by Williams et al similarly showed a high prevalence of CI among Nigerians using the community screening instrument for dementia) and the trail making tests A and B. [23] Our findings are higher than the 20% prevalence rates found in a London clinic [24] and the 17% and 22% found among predialytic and ESRD patients, respectively in California [13] Using the same neuropsychological tool as we did, Etgen et al have reported a lower prevalence of 10.8% at baseline in their prospective cohorts who were inhabitants of Germany. It is therefore possible that there may be racial predisposition to CI.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…However, a recent study by Williams et al similarly showed a high prevalence of CI among Nigerians using the community screening instrument for dementia) and the trail making tests A and B. [23] Our findings are higher than the 20% prevalence rates found in a London clinic [24] and the 17% and 22% found among predialytic and ESRD patients, respectively in California [13] Using the same neuropsychological tool as we did, Etgen et al have reported a lower prevalence of 10.8% at baseline in their prospective cohorts who were inhabitants of Germany. It is therefore possible that there may be racial predisposition to CI.…”
Section: Discussioncontrasting
confidence: 74%
“…[35] Quite surprisingly, age and presence of hypertension showed no association with CI in our study unlike in the previous reports. [24,29] The fact that patients with severely elevated BPs were excluded from the study many have contributed to this finding. Furthermore, this finding is not exclusive.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, patients with early stages of CKD already show cognitive impairment [20]. Depending on CKD stage, CKD is frequently associated with prevalence of cognitive impairment in different domains including executive function, information processing speed, memory and language, which range from 17% to 87% [7,[9][10][11][12][13][14][15].…”
Section: Prevalence Of Chronic Kidney Diseasementioning
confidence: 99%
“…Regarding consequences of CKD, most studies concentrate on cardiovascular morbidity and mortality [6], while cognitive function, which is an important determinant of adherence to CKD therapy, is often overlooked [7]. Cognitive impairment in CKD is getting an increasingly relevant topic for healthcare systems, since CKD prevalence worldwide is estimated to be about 12% [8] and cognitive impairment to affect 17% to 87% of CKD patients, depending on CKD severity [7,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%